Oral lipid-based drug delivery approaches to improve the intestinal lymphatic transport and systemic bioavailability of a highly lipophilic drug cannabidiol - Feng, Wanshan (2022)
Lipid-based formulations play a significant role in oral delivery of lipophilic drugs. Previous studies have shown that natural sesame oil promotes the intestinal lymphatic transport and oral bioavailability of highly lipophilic drug cannabidiol (CBD). However, both lymphatic transport and systemic bioavailability were also associated with considerable variability. The first aim of this thesis was to test the hypothesis that pre-digested lipid formulations (oleic acid, linoleic acid, oleic acid with 2-oleoylglycerol, oleic acid with 2-oleoylglycerol and oleic acid with glycerol) could reduce variability and increase the extent of the intestinal lymphatic transport and oral bioavailability of CBD. In vivo studies in rats showed that pre-digested or purified triglyceride did not improve the lymphatic transport and bioavailability of CBD in comparison to sesame oil. Moreover, the results suggest that both the absorption of lipids and the absorption of co-administered CBD were more efficient following administration of natural sesame oil vehicle compared with pre-digested lipids or purified trioleate. However, this natural oil-based formulation also leads to considerable variability in absorption of CBD [1]. Therefore, the second approach in this thesis was to test the performance of lipid-based formulations with the addition of medium-chain triglyceride (MCT) or surfactants to the sesame oil vehicle in vitro and in vivo using CBD as a model drug. The in vitro lipolysis has shown that addition of the MCT leads to a higher distribution of CBD into the micellar phase. Further addition of surfactants to MCT-containing formulations did not improve distribution of the drug into the micellar phase. In vivo, formulations containing MCT led to lower or similar concentrations of CBD in serum, lymph and mesenteric lymph nodes (MLN), but with reduced variability. MCT improves the emulsification and micellar solubilisation of CBD, but surfactants did not facilitate further the rate and extent of lipolysis. Even though addition of MCT reduces the variability, the in vivo performance for the extent of both lymphatic transport and systemic bioavailability remains superior with a pure natural oil vehicle [2].